Buckling vs. particle desorption in a particle-covered drop subject to compressive surface stresses: a simulation study - Gu, Chuan; Botto, Lorenzo (Soft matter, 2018)
Predicting the behaviour of particle-covered fluid interfaces under compression has implications in several fields. The surface-tension driven adhesion of particles to drops and bubbles is exploited for example to enhance the stability of foams and emulsion and develop new generation materials. When a particle-covered fluid interface is compressed, one can observe either smooth buckling or particle desorption from the interface. The microscopic mechanisms leading to the buckling-to-desorption transition are not fully understood. In this paper we simulate a spherical drop covered by a monolayer of spherical particles. The particle-covered interface is subject to time-dependent compressive surface stresses that mimic the slow deflation of the drop. The buckling-to-desorption transition depends in a non-trivial way on three non-dimensional parameters: the ratio Π s / γ of particle-induced surface pressure and bare surface tension, the ratio a / R of particle and drop radii, and the parameter f characterising the strength of adhesion of each particle to the interface. Based on the insights from the simulations, we propose a configuration diagram describing the effect of these controlling parameters. We find that particle desorption is highly correlated with a mechanical instability that produces small-scale undulations of the monolayer of the order of the particle size that grow when the surface pressure is sufficiently large. We argue that the large local curvature associated with these small undulations can produce large normal forces, enhancing the probability of desorption.